Study of direct alloying of steels by carbon reduction of Cr2O3 under vacuum - Tian-le Song; Zhong-liang Wang; Yan-ping Bao; Chao Gu (Journal of Materials Research and Technology, 2024)
Currently, steel is mainly alloyed by adding ferrochrome alloys in the production of chromium-containing steels. However, the production of ferrochrome consumes a lot of electricity and produces a large number of additional products that are extremely harmful to the environment. For the consideration of the above problems, the experiment studied the reduction behavior of Cr2O3 using carbon powder as the reductant under different ambient pressures, different reductant dosages, and different initial oxygen contents in the molten steel. The results show that CO bubbles can be formed by decreasing the air pressure and increasing the amount of reductant, thus the reduction rate and reduction efficiency of Cr2O3 can be increased. It was found that the ambient air pressure mainly affected the reduction rate of Cr2O3, and the fastest reduction rate of Cr2O3 was found in vacuum environment. The reductant dosage has great influence on the reduction rate, reduction efficiency, density and size of inclusions of Cr2O3. Addition of carbon powder with a carbon-to-oxygen molar ratio of 2 will significantly improve the reduction rate of Cr2O3. The yield of [Cr] in steel can reach more than 95 %. In addition, the density of inclusions in steel is stabilized below 0.2/mm−2. The addition of carbon powder with nc:no ≤ 1.0 significantly reduces the reduction rate of Cr2O3 due to the decrease of carbon concentration in the steel. The density of inclusions in steel also increased significantly up to 210.4/mm−2. The initial oxygen content in the molten steel had little effect on the reduction of Cr2O3. However, the reduction rate of Cr2O3 is lower in steel with high oxygen concentration than in steel with low oxygen concentration. Under the optimum reduction conditions-nc:no = 2.0, initial oxygen content of 3 × 10−4, and ambient air pressure of 50 Pa. The yield of [Cr] in steel can reach 96.85 %, the total oxygen content can be reduced to 1.6 × 10−5, the density of inclusions is 0.04/mm−2, and the size of inclusions is below 1.8 μm.